Steel materials

By incorporating specific elements to suppress austenite recrystallization in steel, the balance between strength and toughness is improved, achieving finer metal structures and increased productivity.

JP7617451B2Active Publication Date: 2025-01-20NIPPON STEEL CORPORATION
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022572887
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-28
Filing Date
2021-04-07
Publication Date
2025-01-20
Estimated Expiration
2041-04-07

AI Technical Summary

Technical Problem

Existing steel materials face a challenge in achieving a balance between recrystallization suppression and toughness, as increasing niobium content for improved recrystallization suppression can lead to excessive strength and reduced toughness.

Method used

Incorporating specific elements such as Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc into the steel composition, within a predetermined range, to suppress or delay austenite recrystallization, thereby shifting the recrystallization start temperature to higher values, allowing for finer metal structures and improved toughness without sacrificing productivity.

Benefits of technology

The solution enables steel materials to maintain high recrystallization suppression while enhancing toughness and productivity, refining the metal structure and reducing manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617451000007
    Figure 0007617451000007
  • Figure 0007617451000008
    Figure 0007617451000008
  • Figure 0007617451000001
    Figure 0007617451000001
Patent Text Reader

Abstract

Provided is a steel material that has a specific chemical composition satisfying 0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0.33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ≧ 0.0003 (where [Pr]、[Sm]、[Eu]、[Gd]、[Tb]、[Dy]、[Ho]、[Er]、[Tm]、[Yb]、[Lu]、[Sc]、[O]、[N]、and [S]are the contents [mass%] of the respective elements).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel material. [Background technology]

[0002] It is generally known that refining the metal structure is effective for improving the material properties required for steel materials. In this regard, in the past, in order to refine the metal structure, for example, the end temperature when hot rolling steel materials, more specifically, when finish rolling, is controlled to suppress the recrystallization of austenite crystal grains, and the driving force of ferrite transformation is increased due to such suppression of recrystallization, thereby generating a large number of new crystals (see, for example, Patent Documents 1 to 4).

[0003] Patent Document 1 teaches that by further adding B in addition to Nb, the recrystallization temperature of austenite increases by 50°C or more, the hardenability improves significantly, and the strength / toughness balance is improved significantly compared to the value expected from a system containing only Nb and B. Patent Documents 2 and 3 state that Nb is an element that is effective in refining austenite grains at high temperatures because it increases the recrystallization temperature. Patent Document 4 states that a small amount of Nb suppresses the recrystallization of austenite and contributes to refining the metal structure. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 58-077528 [Patent Document 2] Japanese Patent Application Publication No. 63-235430 [Patent Document 3] Japanese Patent Application Publication No. 63-235431 [Patent Document 4] JP 2004-269924 A Summary of the Invention [Problem to be solved by the invention]

[0005] Niobium (Nb) is known to be an effective element for suppressing recrystallization, but it also contributes to improving hardenability and precipitation strengthening. Therefore, if the Nb content is increased to obtain a higher recrystallization suppression effect, the strength of the resulting steel material may become too high, and the toughness may decrease accordingly. Therefore, in this technical field, there is a need for steel materials that contain elements other than Nb that have a recrystallization suppression effect similar to or greater than that of Nb, depending on the application in which the steel material is used and the properties required for the application.

[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a steel material having an improved recrystallization suppression effect or improved suppression of recrystallization through a novel configuration. [Means for solving the problem]

[0007] In order to achieve the above object, the present inventors have investigated elements capable of suppressing or delaying the recrystallization of austenite grains. As a result, the present inventors have found that by increasing the amount of a specific element dissolved in steel, it is possible to suppress or delay recrystallization and shift the temperature at which recrystallization starts (hereinafter also simply referred to as the "recrystallization start temperature") to a higher temperature, and have completed the present invention.

[0008] The steel materials that have achieved the above objectives are as follows: (1) In mass percent, C: 0.001 to 1.000%, Si: 0.01 to 3.00%, Mn: 0.10-4.50%, P: 0.300% or less, S: 0.0300% or less, Al: 0.001 to 5.000%, N: 0.2000% or less, O: 0.0100% or less, at least one X element selected from the group consisting of Pr: 0-0.8000%, Sm: 0-0.8000%, Eu: 0-0.8000%, Gd: 0-0.8000%, Tb: 0-0.8000%, Dy: 0-0.8000%, Ho: 0-0.8000%, Er: 0-0.8000%, Tm: 0-0.8000%, Yb: 0-0.8000%, Lu: 0-0.8000%, and Sc: 0-0.8000%, Nb: 0-3.000%, Ti: 0 to 0.500%, Ta: 0 to 0.500%, V: 0~1.00%, Cu: 0-3.00%, Ni: 0-60.00%, Cr: 0~30.00%, Mo: 0-5.00%, W: 0-2.00%, B: 0~0.0200%, Co: 0-3.00%, Be: 0~0.050%, Ag: 0~0.500%, Zr: 0 to 0.5000%, Hf: 0~0.5000%, Ca: 0 to 0.0500%, Mg: 0 to 0.0500%, At least one of La, Ce, Nd, Pm, and Y: 0 to 0.5000% in total; Sn: 0 to 0.300%, Sb: 0 to 0.300%, Te: 0~0.100%, Se: 0~0.100%, As: 0~0.050%, Bi: 0 to 0.500%, Pb: 0 to 0.500%, and The balance is composed of Fe and impurities. A steel material having a chemical composition that satisfies the following formula 1. 0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0. 33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ≧ 0.0003...Equation 1 Here, [Pr], [Sm], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], and [S] are the contents [mass%] of each element, and are 0 when the element is not contained. (2) The chemical composition is, in mass%, Nb: 0.003 to 3.000%, Ti: 0.005 to 0.500%, Ta: 0.001 to 0.500%, V: 0.001 to 1.00%, Cu: 0.001-3.00%, Ni: 0.001 to 60.00%, Cr: 0.001~30.00%, Mo: 0.001 to 5.00%, W: 0.001 to 2.00%, B: 0.0001~0.0200%, Co: 0.001 to 3.00%, Be: 0.0003~0.050%, Ag: 0.001~0.500%, Zr: 0.0001 to 0.5000%, Hf: 0.0001~0.5000%, Ca: 0.0001 to 0.0500%, Mg: 0.0001 to 0.0500%, At least one of La, Ce, Nd, Pm, and Y: 0.0001 to 0.5000% in total; Sn: 0.001 to 0.300%, Sb: 0.001 to 0.300%, Te: 0.001~0.100%, Se: 0.001 to 0.100%, As: 0.001 to 0.050%, Bi: 0.001 to 0.500%, and Pb: 0.001~0.500% The steel material according to (1) above, comprising one or more of the following: Effect of the Invention

[0009] According to the present invention, it is possible to provide a steel product having an improved recrystallization inhibition effect or in which the inhibition of recrystallization is improved. [Brief description of the drawings]

[0010] [Figure 1] 1 is a graph showing test conditions for a compression processing test in an example. [Diagram 2] This is a graph showing the method of determining the softening rate, excerpted from "The state of Nb in the early stages of recovery and recrystallization of hot-worked austenitic structure of steel" by Maruyama Naoki et al., Journal of the Japan Institute of Metals, Vol. 60, No. 11 (1996), pp. 1051-1057. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] <Steel> The steel material according to the embodiment of the present invention has, in mass%, C: 0.001 to 1.000%, Si: 0.01 to 3.00%, Mn: 0.10-4.50%, P: 0.300% or less, S: 0.0300% or less, Al: 0.001 to 5.000%, N: 0.2000% or less, O: 0.0100% or less, at least one X element selected from the group consisting of Pr: 0-0.8000%, Sm: 0-0.8000%, Eu: 0-0.8000%, Gd: 0-0.8000%, Tb: 0-0.8000%, Dy: 0-0.8000%, Ho: 0-0.8000%, Er: 0-0.8000%, Tm: 0-0.8000%, Yb: 0-0.8000%, Lu: 0-0.8000%, and Sc: 0-0.8000%, Nb: 0-3.000%, Ti: 0 to 0.500%, Ta: 0 to 0.500%, V: 0~1.00%, Cu: 0-3.00%, Ni: 0-60.00%, Cr: 0~30.00%, Mo: 0-5.00%, W: 0-2.00%, B: 0~0.0200%, Co: 0-3.00%, Be: 0~0.050%, Ag: 0~0.500%, Zr: 0 to 0.5000%, Hf: 0~0.5000%, Ca: 0 to 0.0500%, Mg: 0 to 0.0500%, At least one of La, Ce, Nd, Pm, and Y: 0 to 0.5000% in total; Sn: 0 to 0.300%, Sb: 0 to 0.300%, Te: 0~0.100%, Se: 0~0.100%, As: 0~0.050%, Bi: 0 to 0.500%, Pb: 0 to 0.500%, and The balance is composed of Fe and impurities. It is characterized by having a chemical composition that satisfies the following formula 1. 0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0. 33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ≧ 0.0003...Equation 1 Here, [Pr], [Sm], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], and [S] are the contents [mass%] of each element, and are 0 when the element is not contained.

[0012] In order to suppress the recrystallization of austenite grains, it is necessary to finish the finish rolling at a low temperature, as described above. However, in this case, it may be necessary to wait until the steel material is cooled to an appropriate temperature before starting the finish rolling, which may result in a decrease in productivity. In particular, when the product is a relatively thick steel material used in applications such as building materials, it may take a considerable amount of time to sufficiently lower the temperature to the center of the steel material before the finish rolling, and in such cases the decrease in productivity is particularly noticeable. For this reason, in order to manufacture steel material without impairing productivity, it is generally desirable to finish the hot rolling at a higher temperature, but on the other hand, it is necessary to suppress recrystallization in order to refine the metal structure.

[0013] Therefore, in order to improve productivity while refining the metal structure, it is necessary to expand the non-recrystallization temperature range, specifically, to raise the temperature at which the recrystallization of austenite grains begins. To explain in more detail, when steel is hot-rolled, the crystals in the steel are crushed by the hot rolling, and the arrangement of Fe atoms that was neatly arranged in the crystals is disturbed, resulting in many discontinuous structures called deformation bands, and many step-like irregularities (ledges) are generated at the grain boundaries. However, if the rolling temperature is high at this time, the Fe atoms will move on their own to eliminate the deformation bands and ledges, and will try to return from the unstable disordered state to a stable crystal in which the Fe atoms are neatly arranged. This is a phenomenon called recrystallization. On the other hand, if the rolling temperature is low (for example, below about 800°C), the Fe atoms cannot move, so the hot rolling ends with ledges and deformation bands remaining at many places on the grain boundaries and within the grains.

[0014] In the cooling process after hot rolling, the metal structure transforms from austenite to ferrite, and such transformation generally occurs at the places where the arrangement of Fe atoms in austenite is disturbed. Therefore, when austenite recrystallizes during hot rolling, the only places where the arrangement of Fe atoms is disturbed are the grain boundaries, so new ferrite crystals can only be generated from the grain boundaries of austenite. On the other hand, when hot rolling is performed at a low temperature, for example, less than about 800°C, it is possible to generate many new ferrite crystals from ledges and deformation bands that exist in many places of austenite. Steel materials whose metal structure is austenite and steel materials whose metal structure is martensite do not transform to ferrite, but by suppressing recrystallization, the strain accumulated in the austenite grains during the hot rolling process increases, and the crystal grains become finer. Thus, hot rolling at a low temperature, more specifically, finish rolling at a low temperature, is very effective in refining the metal structure, but as mentioned above, it is required to finish hot rolling at a higher temperature from the viewpoint of productivity. Therefore, in order to improve productivity while refining the metal structure, it is preferable to increase the recrystallization start temperature.

[0015] Therefore, the present inventors have studied elements that can suppress or delay the recrystallization of austenite grains. As a result, the present inventors have found that by setting the amount of specific elements dissolved in steel, namely, Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc elements (hereinafter also referred to as "X elements") within a predetermined range while taking into consideration the relationship with the inclusions formed by these elements in steel, more specifically, the oxides, nitrides, and sulfides of these elements (i.e., by setting the effective amount of the X element corresponding to the left side of formula 1 to 0.0003% or more), the recrystallization of austenite grains can be suppressed or delayed, and the recrystallization start temperature can be shifted to the high temperature side due to such suppression or delay of recrystallization. Therefore, according to the present invention, even when hot rolling, particularly finish rolling, is performed at a relatively high temperature, a steel material in which recrystallization is significantly suppressed can be obtained, thereby improving productivity and making it possible to refine the metal structure in the finally obtained steel material. As a result, it is possible to improve the properties associated with the refinement of the metal structure, such as toughness, while also reducing the manufacturing costs of the steel material and the number of manufacturing processes.

[0016] Although it is not intended to be bound by any particular theory, it is believed that the above-mentioned X element according to the embodiment of the present invention is fixed to lattice defects such as dislocations introduced into the steel during hot rolling, and for example, inhibits the dislocations from rearranging and moving to a stable arrangement, thereby suppressing recrystallization. Since the above-mentioned X elements all have a larger atomic radius than Nb used in the conventional technology, it is believed that by fixing such elements having a relatively large atomic radius to lattice defects such as dislocations, the effect of inhibiting dislocation rearrangement, etc. can be enhanced, and as a result, it is believed that at least the same or higher recrystallization suppression effect can be achieved compared to conventional steel materials using Nb. Therefore, in the present invention, it can be said that it is extremely important to dissolve a large amount of such elements having a relatively large atomic radius in the steel.

[0017] However, there is a problem that these X elements are likely to combine with O (oxygen), N (nitrogen) and S (sulfur) present in the steel to form inclusions consisting of oxides, nitrides and sulfides. If the X element forms such inclusions in the steel, the amount of the X element in solid solution that can contribute to the inhibition of recrystallization decreases, and the recrystallization inhibition effect obtained by the X element being fixed to lattice defects such as dislocations cannot be fully obtained. In the present invention, the amount of the X element in solid solution taking such inclusions into consideration is calculated as the effective amount of the X element by the above formula 1 described in detail later, and the effective amount is set within a predetermined range, i.e., 0.0003% or more, thereby making it possible to achieve a higher recrystallization inhibition effect.

[0018] As described above, the X element in the present invention is likely to combine with O, N, and S to form inclusions, and therefore it is generally difficult to ensure a predetermined amount of solid solution in steel. For these reasons, the recrystallization suppression effect of the X element was not known in the past. However, with the recent progress in refining technology, it has become possible to reduce the contents of elements such as O, N, and S, which are generally present in steel as impurities, to a very low level, and this time, it has been possible to realize the solid solution of the X element within a predetermined range. Therefore, the recrystallization suppression effect caused by the solid solution of the X element has been revealed for the first time by the present inventors, which is extremely unexpected and surprising.

[0019] Hereinafter, the steel material according to the embodiment of the present invention will be described in more detail. In the following description, the unit of content of each element, "%", means "mass%" unless otherwise specified. In addition, in this specification, "to" indicating a numerical range is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit unless otherwise specified.

[0020] [C:0.001~1.000%] Carbon (C) is an element necessary for stabilizing hardness and / or ensuring strength. To fully obtain these effects, the C content is 0.001% or more. The C content may be 0.005% or more, 0.010% or more, or 0.020% or more. On the other hand, if C is contained excessively, toughness, bendability, and / or weldability may decrease. Therefore, the C content is 1.000% or less. The C content may be 0.800% or less, 0.600% or less, or 0.500% or less.

[0021] [Si: 0.01-3.00%] Silicon (Si) is a deoxidizing element and also contributes to improving strength. To fully obtain these effects, the Si content is 0.01% or more. The Si content may be 0.05% or more, 0.10% or more, or 0.30% or more. On the other hand, excessive Si content may reduce toughness or cause surface quality defects called scale defects. Therefore, the Si content is 3.00% or less. The Si content may be 2.00% or less, 1.00% or less, or 0.60% or less.

[0022] [Mn: 0.10~4.50%] Manganese (Mn) is an element effective in improving hardenability and / or strength, and is also an effective austenite stabilizing element. To fully obtain these effects, the Mn content is 0.10% or more. The Mn content may be 0.50% or more, 0.70% or more, or 1.00% or more. On the other hand, excessive Mn content may generate MnS, which is harmful to toughness, or may reduce oxidation resistance. Therefore, the Mn content is 4.50% or less. The Mn content may be 4.00% or less, 3.50% or less, or 3.00% or less.

[0023] [P:0.300% or less] Phosphorus (P) is an element that is mixed in during the manufacturing process. The P content may be 0%. However, in order to reduce the P content to less than 0.0001%, refining takes time, which leads to a decrease in productivity. Therefore, the P content may be 0.0001% or more, 0.0005% or more, 0.001% or more, 0.003% or more, or 0.005% or more. From the viewpoint of manufacturing costs, the P content may be 0.007% or more. On the other hand, if P is contained excessively, the workability and / or toughness of the steel material may decrease. Therefore, the P content is 0.300% or less. The P content may be 0.100% or less, 0.030% or less, or 0.010% or less.

[0024] [S:0.0300% or less] Sulfur (S) is an element that is mixed in during the manufacturing process, and from the viewpoint of reducing inclusions formed with the X element according to the embodiment of the present invention, the less the better, and therefore the S content may be 0%. However, in order to reduce the S content to less than 0.0001%, refining takes time, which leads to a decrease in productivity. Therefore, the S content may be 0.0001% or more, 0.0005% or more, or 0.0010% or more. On the other hand, if S is contained excessively, the effective amount of the X element decreases and the toughness may decrease. Therefore, the S content is 0.0300% or less. The S content is preferably 0.0100% or less, more preferably 0.0050% or less, and most preferably 0.0030% or less.

[0025] [Al: 0.001-5.000%] Aluminum (Al) is a deoxidizing element and is also an element effective in improving corrosion resistance and / or heat resistance. To obtain these effects, the Al content is 0.001% or more. The Al content may be 0.010% or more, 0.100% or more, or 0.200% or more. In particular, from the viewpoint of sufficiently improving heat resistance, the Al content may be 1.000% or more, 2.000% or more, or 3.000% or more. On the other hand, if Al is contained excessively, coarse inclusions may be generated to reduce toughness, problems such as cracks may occur during the manufacturing process, and / or fatigue resistance properties may be reduced. Therefore, the Al content is 5.000% or less. The Al content may be 4.500% or less, 4.000% or less, or 3.500% or less. In particular, from the viewpoint of suppressing a decrease in toughness, the Al content may be 1.500% or less, 1.000% or less, or 0.300% or less.

[0026] [N:0.2000% or less] Nitrogen (N) is an element that is mixed in during the manufacturing process, and from the viewpoint of reducing inclusions formed with the X element according to the embodiment of the present invention, the less the better, and therefore the N content may be 0%. However, in order to reduce the N content to less than 0.0001%, refining takes time, which leads to a decrease in productivity. Therefore, the N content may be 0.0001% or more, 0.0005% or more, or 0.0010% or more. On the other hand, N is also an element that is effective in stabilizing austenite, and may be intentionally contained as necessary. In this case, the N content is preferably 0.0100% or more, and may be 0.0200% or more, or 0.0500% or more. However, if N is contained excessively, the effective amount of the X element decreases and the toughness may decrease. Therefore, the N content is 0.2000% or less. The N content may be 0.1500% or less, 0.1000% or less, or 0.0800% or less.

[0027] [O:0.0100% or less] Oxygen (O) is an element that is mixed in during the manufacturing process, and from the viewpoint of reducing inclusions formed with the X element according to the embodiment of the present invention, the less the O content, the better, and therefore the O content may be 0%. However, in order to reduce the O content to less than 0.0001%, refining takes time, which leads to a decrease in productivity. Therefore, the O content may be 0.0001% or more, 0.0005% or more, or 0.0010% or more. On the other hand, if O is contained excessively, coarse inclusions are formed, the effective amount of the X element decreases, and the formability and / or toughness of the steel material may decrease. Therefore, the O content is 0.0100% or less. The O content may be 0.0080% or less, 0.0060% or less, or 0.0040% or less.

[0028] [At least one X element selected from the group consisting of Pr: 0-0.8000%, Sm: 0-0.8000%, Eu: 0-0.8000%, Gd: 0-0.8000%, Tb: 0-0.8000%, Dy: 0-0.8000%, Ho: 0-0.8000%, Er: 0-0.8000%, Tm: 0-0.8000%, Yb: 0-0.8000%, Lu: 0-0.8000%, and Sc: 0-0.8000%] The X elements according to the embodiment of the present invention are Pr: 0 to 0.8000%, Sm: 0 to 0.8000%, Eu: 0 to 0.8000%, Gd: 0 to 0.8000%, Tb: 0 to 0.8000%, Dy: 0 to 0.8000%, Ho: 0 to 0.8000%, Er: 0 to 0.8000%, Tm: 0 to 0.8000%, Yb: 0 to 0.8000%, Lu: 0 to 0.8000%, and Sc: 0 to 0.8000%. Praseodymium (Pr), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), and scandium (Sc) can exhibit a recrystallization suppression effect by existing in austenite in a solid solution state. By exhibiting the recrystallization suppression effect, even when hot rolling, particularly finish rolling, is performed at a relatively high temperature, the metal structure in the finally obtained steel material can be refined, so that it is possible to improve the toughness evaluated by, for example, Charpy impact properties, and to significantly improve productivity.

[0029] The X element may be any one element alone, or any specific combination of two or more of the elements. The X element may be present in an amount that satisfies formula 1, which will be described in detail later, and the lower limit is not particularly limited. However, for example, the content of each X element or the total content may be 0.0010% or more, preferably 0.0050% or more, more preferably 0.0150% or more, even more preferably 0.0300% or more, and most preferably 0.0500% or more. On the other hand, even if the X element is contained excessively, the effect is saturated, and therefore, the inclusion of the X element in the steel material more than necessary may lead to an increase in manufacturing costs. Therefore, the content of each X element may be 0.8000% or less, for example, 0.7000% or less, 0.6000% or less, 0.5000% or less, 0.4000% or less, or 0.3000% or less. The total content of the X elements is 9.6000% or less, and may be, for example, 6.0000% or less, 5.0000% or less, 4.0000% or less, 2.0000% or less, 1.0000% or less, or 0.5000% or less.

[0030] The basic chemical composition of the steel material according to the embodiment of the present invention is as described above. Furthermore, the steel material may contain one or more of the following optional elements as necessary. For example, the steel material may contain one or more of Nb: 0-3.000%, Ti: 0-0.500%, Ta: 0-0.500%, V: 0-1.00%, Cu: 0-3.00%, Ni: 0-60.00%, Cr: 0-30.00%, Mo: 0-5.00%, W: 0-2.00%, B: 0-0.0200%, Co: 0-3.00%, Be: 0-0.050%, and Ag: 0-0.500%. The steel material may contain one or more of Zr: 0-0.5000%, Hf: 0-0.5000%, Ca: 0-0.0500%, Mg: 0-0.0500%, and at least one of La, Ce, Nd, Pm, and Y: 0-0.5000% in total. The steel material may contain one or two of Sn: 0-0.300% and Sb: 0-0.300%. The steel material may contain one or two of Te: 0-0.100%, Se: 0-0.100%, As: 0-0.050%, Bi: 0-0.500%, and Pb: 0-0.500%. These optional elements will be described in detail below.

[0031] [Nb:0~3.000%] Niobium (Nb) is an element that contributes to precipitation strengthening and suppression of recrystallization. The Nb content may be 0%, but in order to obtain these effects, the Nb content is preferably 0.003% or more. For example, the Nb content may be 0.005% or more or 0.010% or more. In particular, from the viewpoint of sufficiently achieving precipitation strengthening, the Nb content may be 1.000% or more or 1.500% or more. On the other hand, if Nb is contained excessively, the effect becomes saturated and the workability and / or toughness may be reduced. Therefore, the Nb content is 3.000% or less. The Nb content may be 2.800% or less, 2.500% or less, or 2.000% or less. In particular, from the viewpoint of suppressing the decrease in toughness of the weld heat affected zone (HAZ), the Nb content is preferably 0.100% or less, and may be 0.080% or less, 0.050% or less, or 0.030% or less.

[0032] [Ti: 0~0.500%] Titanium (Ti) is an element that contributes to improving the strength of steel materials by precipitation strengthening and the like. The Ti content may be 0%, but in order to obtain such an effect, the Ti content is preferably 0.005% or more. The Ti content may be 0.010% or more, 0.050% or more, or 0.080% or more. On the other hand, if Ti is contained excessively, a large amount of precipitates may be generated, which may reduce toughness. Therefore, the Ti content is 0.500% or less. The Ti content may be 0.300% or less, 0.200% or less, or 0.100% or less.

[0033] [Ta: 0~0.500%] Tantalum (Ta) is an element effective for controlling the morphology of carbides and increasing strength. The Ta content may be 0%, but in order to obtain these effects, the Ta content is preferably 0.001% or more. The Ta content may be 0.005% or more, 0.010% or more, or 0.050% or more. On the other hand, if Ta is contained excessively, a large number of fine Ta carbides are precipitated, which leads to an excessive increase in the strength of the steel material, and as a result, there are cases in which the ductility and cold workability are reduced. Therefore, the Ta content is 0.500% or less. The Ta content may be 0.300% or less, 0.100% or less, or 0.080% or less.

[0034] [V:0~1.00%] Vanadium (V) is an element that contributes to improving the strength of steel materials by precipitation strengthening and the like. The V content may be 0%, but in order to obtain such an effect, the V content is preferably 0.001% or more. The V content may be 0.01% or more, 0.02% or more, 0.05% or more, or 0.10% or more. On the other hand, if V is contained excessively, a large amount of precipitates may be generated, which may reduce toughness. Therefore, the V content is 1.00% or less. The V content may be 0.80% or less, 0.60% or less, or 0.50% or less.

[0035] [Cu: 0-3.00%] Copper (Cu) is an element that contributes to improving strength and / or corrosion resistance. The Cu content may be 0%, but in order to obtain these effects, the Cu content is preferably 0.001% or more. The Cu content may be 0.01% or more, 0.10% or more, 0.15% or more, 0.20% or more, or 0.30% or more. On the other hand, excessive Cu content may cause deterioration of toughness and weldability. Therefore, the Cu content is 3.00% or less. The Cu content may be 2.00% or less, 1.50% or less, 1.00% or less, or 0.50% or less.

[0036] [Ni:0~60.00%] Nickel (Ni) is an element that contributes to improving strength and / or heat resistance, and is also an effective austenite stabilizing element. The Ni content may be 0%, but in order to obtain these effects, the Ni content is preferably 0.001% or more. The Ni content may be 0.01% or more, 0.10% or more, 0.50% or more, 0.70% or more, 1.00% or more, or 3.00% or more. In particular, from the viewpoint of sufficiently improving heat resistance, the Ni content may be 30.00% or more, 35.00% or more, or 40.00% or more. On the other hand, excessive Ni content may increase the alloy cost as well as the deformation resistance during hot working, and the equipment load may become large. Therefore, the Ni content is 60.00% or less. The Ni content may be 55.00% or less, or 50.00% or less. In particular, from the viewpoint of economy and / or suppressing a decrease in weldability, the Ni content may be 15.00% or less, 10.00% or less, 6.00% or less, or 4.00% or less.

[0037] [Cr:0~30.00%] Chromium (Cr) is an element that contributes to improving strength and / or corrosion resistance. The Cr content may be 0%, but in order to obtain these effects, the Cr content is preferably 0.001% or more. The Cr content may be 0.01% or more, 0.05% or more, 0.10% or more, or 0.50% or more. In particular, from the viewpoint of sufficiently improving corrosion resistance, the Cr content may be 10.00% or more, 12.00% or more, or 15.00% or more. On the other hand, excessive Cr content may increase the alloy cost and may decrease the toughness. Therefore, the Cr content is 30.00% or less. The Cr content may be 28.00% or less, 25.00% or less, or 20.00% or less. In particular, from the viewpoint of suppressing the decrease in weldability and / or workability, the Cr content may be 10.00% or less, 9.00% or less, or 7.50% or less.

[0038] [Mo:0~5.00%] Molybdenum (Mo) is an element that improves the hardenability of steel, contributes to improving strength, and also contributes to improving corrosion resistance. The Mo content may be 0%, but in order to obtain these effects, the Mo content is preferably 0.001% or more. The Mo content may be 0.01% or more, 0.02% or more, 0.50% or more, or 1.00% or more. On the other hand, if Mo is contained excessively, the deformation resistance during hot working increases, and the equipment load may become large. Therefore, the Mo content is 5.00% or less. The Mo content may be 4.50% or less, 4.00% or less, 3.00% or less, or 1.50% or less.

[0039] [W:0~2.00%] Tungsten (W) is an element that improves the hardenability of steel and contributes to improving strength. The W content may be 0%, but in order to obtain such an effect, the W content is preferably 0.001% or more. The W content may be 0.01% or more, 0.02% or more, 0.05% or more, 0.10% or more, or 0.50% or more. On the other hand, if W is contained excessively, ductility and weldability may decrease. Therefore, the W content is 2.00% or less. The W content may be 1.80% or less, 1.50% or less, or 1.00% or less.

[0040] [B:0~0.0200%] Boron (B) is an element that contributes to improving strength. The B content may be 0%, but in order to obtain such an effect, the B content is preferably 0.0001% or more. The B content may be 0.0003% or more, 0.0005% or more, or 0.0007% or more. On the other hand, if B is contained excessively, toughness and / or weldability may decrease. Therefore, the B content is 0.0200% or less. The B content may be 0.0100% or less, 0.0050% or less, 0.0030% or less, or 0.0020% or less.

[0041] [Co: 0-3.00%] Cobalt (Co) is an element that contributes to improving hardenability and / or heat resistance. The Co content may be 0%, but in order to obtain these effects, the Co content is preferably 0.001% or more. The Co content may be 0.01% or more, 0.02% or more, 0.05% or more, 0.10% or more, or 0.50% or more. On the other hand, excessive Co content may deteriorate hot workability and lead to an increase in raw material costs. Therefore, the Co content is 3.00% or less. The Co content may be 2.50% or less, 2.00% or less, 1.50% or less, or 0.80% or less.

[0042] [Be:0~0.050%] Beryllium (Be) is an element effective in increasing the strength of the base material and refining the structure. The Be content may be 0%, but in order to obtain such an effect, the Be content is preferably 0.0003% or more. The Be content may be 0.0005% or more, 0.001% or more, or 0.010% or more. On the other hand, if Be is contained excessively, the formability may decrease. Therefore, the Be content is 0.050% or less. The Be content may be 0.040% or less, 0.030% or less, or 0.020% or less.

[0043] [Ag:0~0.500%] Silver (Ag) is an element effective in increasing the strength of the base material and refining the structure. The Ag content may be 0%, but in order to obtain such an effect, the Ag content is preferably 0.001% or more. The Ag content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, if Ag is contained excessively, the formability may decrease. Therefore, the Ag content is 0.500% or less. The Ag content may be 0.400% or less, 0.300% or less, or 0.200% or less.

[0044] [Zr:0~0.5000%] Zirconium (Zr) is an element that can control the morphology of sulfides. The Zr content may be 0%, but in order to obtain such an effect, the Zr content is preferably 0.0001% or more. On the other hand, even if Zr is contained in excess, the effect saturates, and therefore, the inclusion of more Zr than necessary in steel may lead to an increase in manufacturing costs. Therefore, the Zr content is 0.5000% or less.

[0045] [Hf:0~0.5000%] Hafnium (Hf) is an element that can control the morphology of sulfides. The Hf content may be 0%, but in order to obtain such an effect, the Hf content is preferably 0.0001% or more. On the other hand, even if an excessive amount of Hf is contained, the effect is saturated, and therefore, the inclusion of more Hf than necessary in steel may lead to an increase in manufacturing costs. Therefore, the Hf content is 0.5000% or less.

[0046] [Ca: 0~0.0500%] Calcium (Ca) is an element that can control the morphology of sulfides. The Ca content may be 0%, but in order to obtain such an effect, the Ca content is preferably 0.0001% or more. On the other hand, even if an excessive amount of Ca is contained, the effect is saturated, and therefore, the inclusion of more Ca than necessary in the steel material may lead to an increase in manufacturing costs. Therefore, the Ca content is 0.0500% or less.

[0047] [Mg: 0~0.0500%] Magnesium (Mg) is an element capable of controlling the morphology of sulfides. The Mg content may be 0%, but in order to obtain such an effect, the Mg content is preferably 0.0001% or more. The Mg content may be more than 0.0015%, 0.0016% or more, 0.0018% or more, or 0.0020% or more. On the other hand, even if Mg is excessively contained, the effect becomes saturated, and the cold formability and / or toughness may decrease due to the formation of coarse inclusions. Therefore, the Mg content is 0.0500% or less. The Mg content may be 0.0400% or less, 0.0300% or less, or 0.0200% or less.

[0048] [At least one of La, Ce, Nd, Pm and Y: 0 to 0.5000% in total] Lanthanum (La), cerium (Ce), neodymium (Nd), promethium (Pm) and yttrium (Y) are elements that can control the morphology of sulfides, similar to Ca and Mg. The total content of at least one of La, Ce, Nd, Pm and Y may be 0%, but in order to obtain such an effect, it is preferable that it is 0.0001% or more. The total content of at least one of La, Ce, Nd, Pm and Y may be 0.0002% or more, 0.0003% or more, or 0.0004% or more. On the other hand, even if these elements are contained excessively, the effect may be saturated, and coarse oxides or the like may be formed, resulting in a decrease in cold formability. Therefore, the total content of at least one of La, Ce, Nd, Pm and Y may be 0.5000% or less, 0.4000% or less, 0.3000% or less, or 0.2000% or less.

[0049] [Sn: 0~0.300%] Tin (Sn) is an element effective in improving corrosion resistance. The Sn content may be 0%, but in order to obtain such an effect, the Sn content is preferably 0.001% or more. The Sn content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, excessive Sn content may lead to a decrease in toughness, particularly low-temperature toughness. Therefore, the Sn content is 0.300% or less. The Sn content may be 0.250% or less, 0.200% or less, or 0.150% or less.

[0050] [Sb: 0~0.300%] Antimony (Sb) is an element effective for improving corrosion resistance like Sn, and the effect can be increased by including it in combination with Sn. The Sb content may be 0%, but in order to obtain the effect of improving corrosion resistance, the Sb content is preferably 0.001% or more. The Sb content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, excessive Sb content may cause a decrease in toughness, particularly low-temperature toughness. Therefore, the Sb content is 0.300% or less. The Sb content may be 0.250% or less, 0.200% or less, or 0.150% or less.

[0051] [Te:0~0.100%] Tellurium (Te) is an element that is effective in improving the machinability of steel because it forms a low melting point compound with Mn, S, etc. to enhance the lubricating effect. The Te content may be 0%, but in order to obtain such an effect, the Te content is preferably 0.001% or more. The Te content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.040% or more. On the other hand, if Te is contained excessively, the effect becomes saturated and the alloy cost increases. Therefore, the Te content is 0.100% or less. The Te content may be 0.090% or less, 0.080% or less, or 0.070% or less.

[0052] [Se: 0~0.100%] Selenium (Se) is an effective element for improving the machinability of steel because selenides formed in steel change the shear plastic deformation of the workpiece and make chips more likely to be crushed. The Se content may be 0%, but in order to obtain such an effect, the Se content is preferably 0.001% or more. The Se content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.040% or more. On the other hand, if Se is contained excessively, the effect saturates and the alloy cost increases. Therefore, the Se content is 0.100% or less. The Se content may be 0.090% or less, 0.080% or less, or 0.070% or less.

[0053] [As: 0~0.050%] Arsenic (As) is an element effective in improving the machinability of steel. The As content may be 0%, but in order to obtain such an effect, the As content is preferably 0.001% or more. The As content may be 0.005% or more or 0.010% or more. On the other hand, if As is contained excessively, hot workability may be reduced. Therefore, the As content is 0.050% or less. The As content may be 0.040% or less, 0.030% or less, or 0.020% or less.

[0054] [Bi: 0~0.500%] Bismuth (Bi) is an element effective in improving the machinability of steel. The Bi content may be 0%, but in order to obtain such an effect, the Bi content is preferably 0.001% or more. The Bi content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, if Bi is contained excessively, the effect saturates and the alloy cost increases. Therefore, the Bi content is 0.500% or less. The Bi content may be 0.400% or less, 0.300% or less, or 0.200% or less.

[0055] [Pb: 0~0.500%] Lead (Pb) is an element effective in improving the machinability of steel because it melts when the temperature rises during cutting and promotes the development of cracks. The Pb content may be 0%, but in order to obtain such an effect, the Pb content is preferably 0.001% or more. The Pb content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, if Pb is contained excessively, hot workability may be reduced. Therefore, the Pb content is 0.500% or less. The Pb content may be 0.400% or less, 0.300% or less, or 0.200% or less.

[0056] In the steel material according to the embodiment of the present invention, the balance other than the above elements consists of Fe and impurities. The impurities are components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, when the steel material is industrially manufactured.

[0057] [Effective amount of element X] According to an embodiment of the present invention, the effective amount of X element consisting of Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc is determined by the left side of the following formula 1, and the value satisfies the following formula 1. 0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0. 33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ≧ 0.0003...Equation 1 Here, [Pr], [Sm], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], and [S] are the contents [mass%] of each element, and are 0 when the element is not contained.

[0058] By making the effective amount of the X element satisfy the above formula 1, the amount of these elements present in the steel in a solid solution state can be increased, so that the recrystallization of austenite grains can be suppressed or delayed, and the recrystallization start temperature can be shifted to a higher temperature due to such suppression or delay of recrystallization. To explain in more detail, these X elements (hereinafter, also simply referred to as "X") tend to combine with O (oxygen), N (nitrogen) and S (sulfur) present in the steel to form inclusions consisting of oxides (X2O3), nitrides (XN) and sulfides (XS). Once such inclusions are formed, at least the X elements in these inclusions cannot contribute to suppressing the recrystallization of austenite grains. Therefore, in order to suppress the recrystallization of austenite grains, it is necessary to increase the amount of X elements present in the steel in a solid solution state without forming inclusions (i.e., the amount of X elements in the steel).

[0059] Here, the amount of the X element in solid solution in steel can be roughly calculated by subtracting the maximum amount that can be consumed to form inclusions (oxides, nitrides, and sulfides) from the amount of the X element contained in the steel. Therefore, in the embodiment of the present invention, the amount of the X element in solid solution roughly calculated in this manner is the amount of the X element effective for suppressing the recrystallization of austenite grains (i.e., the "effective amount of the X element"), and is specifically defined by the following formula A. Effective amount of element X [atomic %] = Σ(M [Fe] / M [X] )×[X]-(M [Fe] / M [O] )×[O]×2 / 3-(M [Fe] / M [N] )×[N]-(M [Fe] / M [S] )×[S]...Formula A Here, X represents each of the X elements Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc, and M [X] is the atomic weight of element X, M [Fe] is the atomic weight of Fe, M [O] is the atomic weight of O, M [N] is the atomic weight of N, M [S] represents the atomic weight of S, and [X], [O], [N] and [S] are the contents [mass %] of the corresponding elements, and are 0 when the element is not contained.

[0060] The above formula A will be explained in detail below. First, although various alloy elements are contained in the steel material according to the embodiment of the present invention, it is clear that the steel material as a whole is composed almost entirely of Fe, or, when the optional elements Ni and / or Cr are contained relatively in large amounts (the maximum contents are 60.00% and 30.00%, respectively), the steel material is composed almost entirely of Ni and / or Cr in addition to Fe. On the other hand, it is well known that the atomic weights of Ni and Cr are equivalent to the atomic weight of Fe. For this reason, even if the steel material contains a relatively large amount of Ni and / or Cr, the atomic % of each of the X elements Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc can be approximately calculated by multiplying the content [mass %] of each X element by the ratio of the atomic weight of Fe to the atomic weight of each X element, that is, (M [Fe] / M [X] ) × [X]. Therefore, (M [Fe] / M [X] ) × [X], i.e., Σ(M [Fe] / M [X] ) × [X], the atomic percentage of all X elements can be calculated.

[0061] Next, by subtracting the maximum amount (atomic %) that can be consumed to form oxides (X2O3), nitrides (XN) and sulfides (XS) from the total atomic % of X element, the amount of X element in steel that can effectively act to suppress recrystallization of austenite grains can be calculated. Here, for the same reason as explained above, the maximum amount (atomic %) of X element that can be consumed to form oxides (X2O3), nitrides (XN) and sulfides (XS) can be approximately calculated as (M) using the atomic weights of Fe, O, N and S in steel and the contents of O, N and S, respectively. [Fe] / M [o] ) × [O] × 2 / 3, (M [Fe] / M [N] ) × [N], and (M [Fe] / M [S] )×[S]. Therefore, the effective amount of the X element for suppressing the recrystallization of austenite grains can be defined by the following formula A. Effective amount of element X [atomic %] = Σ(M [Fe] / M [X] )×[X]-(M [Fe] / M [O] )×[O]×2 / 3-(M [Fe] / M [N] )×[N]-(M [Fe] / M [S] )×[S]...Formula A

[0062] Here, the atomic weights of Fe, O, N, S and each X element are Fe: 55.845, O: 15.9994, N: 14.0069, S: 32.068, Pr: 140.908, Sm: 150.36, Eu: 151.964, Gd: 157.25, Tb: 158.925, Dy: 162.500, Ho: 164.930, Er: 167.259, Tm: 168.934, Yb: 173.045, Lu: 174.967, Sc: 44.9559. Therefore, by substituting the atomic weights of each element into the above formula A and rearranging it, the effective amount of the X element in atomic % can be approximately expressed by the following formula B. Effective amount = 0.40[Pr] + 0.37[Sm] + 0.37[Eu] + 0.36[Gd] + 0.35[Tb] + 0.34[Dy] + 0.34[Ho] + 0.33[Er] + 0.33[Tm] + 0.32[Yb] + 0.32[Lu] + 1.24[Sc] - 2.33[O] - 3.99[N] - 1.74[S] Formula B Here, [Pr], [Sm], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], and [S] are the contents [mass%] of each element, and are 0 when the element is not contained.

[0063] In an embodiment of the present invention, in order to suppress the recrystallization of austenite grains, the effective amount of the X element calculated by the above formula B must be 0.0003% or more, that is, must satisfy the following formula 1. 0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0. 33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ≧ 0.0003...Equation 1 The effective amount of the X element may be, for example, 0.0005% or more or 0.0007% or more, preferably 0.0010% or more, more preferably 0.0015% or more, even more preferably 0.0030% or more, and most preferably 0.0050% or more or 0.0100% or more. Also, as is clear from the above formula 1, in order to stably secure the effective amount, it is preferable to reduce the contents of O, N and S in the steel as much as possible. Here, the upper limit of the effective amount of the X element is not particularly limited, but even if the effective amount of the X element is excessively increased, the effect becomes saturated and the manufacturing cost increases (the alloy cost increases with the increase in the content of the X element and / or the refining cost increases for O, N and S), which is not necessarily preferable. Therefore, the effective amount of the X element is preferably 2.0000% or less, and may be, for example, 1.8000% or less, 1.5000% or less, 1.2000% or less, 1.0000% or less, or 0.8000% or less.

[0064] The steel material according to the embodiment of the present invention may be any steel material and is not particularly limited. The steel material according to the embodiment of the present invention includes, for example, steel material before exerting the recrystallization suppression effect, such as slab, billet, bloom, which is a steel material before hot rolling, and steel material after exerting the recrystallization suppression effect, such as steel material after hot rolling. The steel material after hot rolling is not particularly limited, but includes, for example, thick steel plate, thin steel plate, and further, steel bar, wire rod, shaped steel, steel pipe, etc.

[0065] The steel material according to the embodiment of the present invention can be manufactured by any suitable method known to those skilled in the art depending on the form of the final product, etc. For example, when the steel material is a thick steel plate, the manufacturing method thereof includes the steps generally applied in manufacturing a thick steel plate, for example, the step of casting a slab having the above-described chemical composition, the step of hot rolling the cast slab, which includes a finish rolling that is completed at a temperature lower than the recrystallization start temperature, and the step of cooling the obtained rolled material, and may further include an appropriate heat treatment step and a tempering step, etc., as necessary. For example, the steel material according to the embodiment of the present invention is particularly suitable for applying a thermomechanical control process (TMCP) that combines controlled rolling and accelerated cooling.

[0066] In addition, when the steel material is a thin steel plate, the manufacturing method thereof includes steps generally applied when manufacturing a thin steel plate, for example, a step of casting a slab having the above-described chemical composition, a step of hot rolling the cast slab, including a finish rolling step that ends at a temperature lower than the recrystallization start temperature, and a step of cooling and coiling the obtained rolled material, and may further include a cold rolling step, an annealing step, etc. as necessary. Similarly, the manufacturing method of steel bars and other steel materials includes steps generally applied when manufacturing steel bars and other steel materials, for example, a steelmaking step of forming molten steel having the above-described chemical composition, a step of casting slabs, billets, blooms, etc. from the formed molten steel, a step of hot rolling the cast slabs, billets, blooms, etc., including a finish rolling step that ends at a temperature lower than the recrystallization start temperature, and a step of cooling the obtained rolled material, and other steps can be appropriately selected and performed from appropriate steps known to those skilled in the art for manufacturing those steel materials. The specific conditions for each of the above steps are not particularly limited, and appropriate conditions may be appropriately selected depending on the type of steel, the type and shape of the steel material, etc. In the production of the steel material according to the embodiment of the present invention, it is important to ensure an effective amount of the X element, and for this purpose, it is extremely important to sufficiently reduce the contents of O, N, and S, which can form inclusions in the steel together with the X element, in the refining step.

[0067] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. EXAMPLES

[0068] In this example, first, molten steels having various chemical compositions were melted using a vacuum melting furnace, and ingots of about 50 kg were produced by the ingot casting method. The chemical compositions of samples taken from each of the obtained ingots were analyzed and shown in Table 1 below. Next, a compression test was carried out using cylindrical test pieces (φ8 mm × height 12 mm) obtained from the ingots, and the recrystallization inhibition effect of the steel material was evaluated based on the softening rate calculated from the results of the test.

[0069] Specifically, according to the test conditions for the compression processing test shown in Figure 1, first, the cylindrical test material was heated to 950 to 1300 °C, and then the compression temperature was 950 °C, the true strain ε = 0.4, and the strain rate ε / t = 5 s -1 Two compression tests were performed under conditions of 10 s, 100 s pass time, and 10 s interpass time (Process 1 and Process 2 in Figure 1), and the softening rate was measured from the stress-strain curves measured by Process 1 and Process 2. To explain in more detail, as shown in Figure 2 (excerpt from Maruyama Naoki et al., "State of Nb in the Early Stage of Recovery and Recrystallization of Hot-Worked Austenitic Structure of Steel," Journal of the Japan Institute of Metals, Vol. 60, No. 11 (1996), pp. 1051-1057), the yield stresses during the first and second compression processes are σ1 and σ2, respectively, and the maximum stress during the first compression process is σ m In this case, the softening rate X s can be calculated from the following formula: X s =(σ m -σ2) / (σ m -σ1)

[0070] If sufficient recrystallization has progressed between the first and second compression processes, the stress-strain curves measured by processes 1 and 2 will show similar behavior, and σ2 will be close to σ1. Therefore, the softening rate X sOn the other hand, if the progress of recrystallization is suppressed between the first and second compression processes, the dislocation density increases during the second compression process, causing work hardening, and the yield stress σ2 increases, resulting in a lower softening rate X s Therefore, the softening rate of steel, X s By measuring the softening rate X, it is possible to evaluate the recrystallization suppression effect of the steel material. s The steel was evaluated as having an improved recrystallization inhibition effect when the value of the recrystallization inhibition coefficient was 0.20 or less. The results are shown in Table 1 below.

[0071] [Table 1-1]

[0072] [Table 1-2]

[0073] [Table 1-3]

[0074] [Table 1-4]

[0075] [Table 1-5]

[0076] [Table 1-6]

[0077] Referring to Table 1, in Comparative Examples 84 to 91, the effective amount of the X element consisting of Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc was low, so that sufficient recrystallization suppression effect could not be exhibited. More specifically, in Comparative Example 84, since the X element was not contained, sufficient recrystallization suppression effect could not be exhibited. In addition, in Comparative Examples 85 to 91, although the above-mentioned X element was contained, its content was low in a relative relationship with O, N, and / or S, in other words, the content of O, N, and / or S was excessive with respect to the X element, so that it is considered that a relatively large amount of inclusions was generated between the X element and these elements. As a result, the effective amount of the X element was low, and sufficient recrystallization suppression effect could not be exhibited. In contrast to this, in all the examples according to the present invention, a high recrystallization suppression effect could be exhibited by setting the effective amount of the X element to 0.0003% or more. [Industrial Applicability]

[0078] The steel material according to the embodiment of the present invention is, for example, a slab, a billet, or a bloom, which is a steel material before hot rolling, or a steel material after hot rolling. The steel material after hot rolling includes, for example, a thick steel plate used for applications such as bridges, architecture, shipbuilding, and pressure vessels, a thin steel plate used for applications such as automobiles and home appliances, and further includes a steel bar, a wire rod, a shaped steel, and a steel pipe. When the steel material according to the embodiment of the present invention is applied to these materials, the steel material can be manufactured without impairing productivity due to the recrystallization suppression effect, and the metal structure in the steel material can be refined, so that the properties related to the refinement of such a metal structure, such as toughness, can be significantly improved.

Claims

1. In mass percent, C: 0.001-1.000%, Si: 0.01-3.00%, Mn: 0.10 to 4.50%, P: 0.300% or less, S: 0.0300% or less, Al: 0.001-5.000%, N: 0.2000% or less, O: 0.0100% or less, at least one X element selected from the group consisting of Pr: 0 to 0.8000%, Eu: 0 to 0.8000%, Gd: 0 to 0.8000%, Tb: 0 to 0.8000%, Dy: 0 to 0.8000%, Ho: 0 to 0.8000%, Er: 0 to 0.8000%, Tm: 0 to 0.8000%, Yb: 0 to 0.8000%, Lu: 0 to 0.8000%, and Sc: 0 to 0.8000%, Nb: 0 to 3.000%, Ti: 0 to 0.500%, Ta: 0-0.500%, V: 0-1.00%, Cu: 0-3.00%, Ni: 0 to 60.00%, Cr: 0-10.00%, Mo: 0-5.00%, W: 0-2.00%, B: 0-0.0200%, Co: 0-3.00%, Be: 0 to 0.050%, Ag: 0-0.500%, Zr: 0 to 0.5000%, Hf: 0-0.5000%, Ca: 0-0.0500%, Mg: 0 to 0.0500% (excluding 0.0001 to 0.0015%) At least one of La, Ce, Nd, Pm, and Y: 0 to 0.5000% in total, Sn: 0-0.300%, Sb: 0 to 0.300%, Te: 0 to 0.100%, Se: 0 to 0.100%, As: 0 to 0.050%, Bi: 0-0.500%, Pb: 0 to 0.500%, and The balance is composed of Fe and impurities. A steel material having a chemical composition that satisfies the following formula 1. 0.40[Pr]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0.33[Er] ]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ≧ 0.0003 ... Formula 1 Here, [Pr], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], and [S] are the contents [mass %] of each element, and are 0 when the element is not contained.

2. The chemical composition, in mass%, Nb: 0.003 to 3.000%, Ti: 0.005-0.500%, Ta: 0.001 to 0.500%, V: 0.001-1.00%, Cu: 0.001 to 3.00%, Ni: 0.001 to 60.00%, Cr: 0.001 to 10.00%, Mo: 0.001 to 5.00%, W: 0.001-2.00%, B: 0.0001 to 0.0200%, Co: 0.001-3.00%, Be: 0.0003 to 0.050%, and Ag: 0.001-0.500% The steel material according to claim 1, comprising one or more of the following:

3. The chemical composition, in mass%, Zr: 0.0001 to 0.5000%, Hf: 0.0001-0.5000%, Ca: 0.0001-0.0500%, Mg: 0.0001 to 0.0500% (excluding 0.0001 to 0.0015%), and At least one of La, Ce, Nd, Pm, and Y: 0.0001 to 0.5000% in total The steel material according to claim 1 or 2, comprising one or more of the following:

4. The chemical composition, in mass%, Sn: 0.001 to 0.300%, and Sb: 0.001-0.300% The steel material according to any one of claims 1 to 3, comprising one or two of the following:

5. The chemical composition, in mass%, Te: 0.001 to 0.100%, Se: 0.001-0.100%, As: 0.001 to 0.050%, Bi: 0.001 to 0.500%, and Pb: 0.001-0.500% The steel material according to any one of claims 1 to 4, comprising one or more of the following:

Citation Information

Patent Citations

  • Manufacture of high tensile steel with superior toughness at low temperature

    JP1983077528A

  • Manufacture of tempered high-tensile steel stock excellent in toughness and weldability

    JP1988235430A

  • Manufacture of steel plate excellent in strength and toughness and reduced in acoustic anisotropy

    JP1988235431A

  • High efficient producing method of steel sheet excellent in strength and toughness

    JP2004269924A

  • Annealing method of tool steel, production method of annealed material for tool steel, annealed material for tool steel, tool steel using the same and tool

    JP2005226150A